Alcohol Suppresses the Granulopoietic Response to Pulmonary S. Pneumoniae Infection with Enhancement of STAT3 Signaling() - Siggins, Robert W. (2011)
Enhanced granulopoietic activity is crucial for host defense against bacterial pneumonia. Alcohol impairs this response. The underlying mechanisms remain obscure. Granulocyte colony-stimulating factor (G-CSF) produced by infected lung tissue plays a key role in stimulating bone marrow granulopoiesis. This study investigated the effects of alcohol on G-CSF signaling in the regulation of marrow myeloid progenitor cell proliferation in mice with Streptococcus pneumoniae pneumonia. Chronic alcohol consumption plus acute alcohol intoxication suppressed the increase in blood granulocyte counts following intrapulmonary challenge with S. pneumoniae. This suppression was associated with a significant decrease in bone marrow granulopoietic progenitor cell proliferation. Alcohol treatment significantly enhanced STAT3 phosphorylation in bone marrow cells of animals challenged with S. pneumoniae. In vitro experiments showed that G-CSF-induced activation of STAT3-p27(Kip1) pathway in murine myeloid progenitor cell line 32D-G-CSFR cells was markedly enhanced by alcohol exposure. Alcohol dose-dependently inhibited G-CSF-stimulated 32D-G-CSFR cell proliferation. This impairment of myeloid progenitor cell proliferation was not attenuated by inhibition of alcohol metabolism through either the alcohol dehydrogenase pathway or the CYP450 system. These data suggest that alcohol enhances G-CSF-associated STAT3-p27(Kip1) signaling, which impairs granulopoietic progenitor cell proliferation by inducing cell cycling arrest and facilitating their terminal differentiation during the granulopoietic response to pulmonary infection.